Sharing the economy in tourism and sustainable city development in the light of agenda 2030 - Daria Elżbieta Jaremen; Elżbieta Nawrocka; Michał Żemła (Economies, 2019)
The dynamic development of the sharing economy is clearly seen in particular, in the area of tourism in large cities. There is, therefore, an increasingly urgent need to study its impact on the functioning of cities, especially when they implement a sustainable development policy. Therefore,the need to study its impact on cities' performances is more and more urgent, particularly, when they implement a sustainable development policy. This study discussed the influence of a sharing economy in tourism on city sustainability from the perspective of the Agenda 2030 goals. The main objective of the paper was achieved, thanks to in-depth analysis of the content of secondary sources. Results of the analysis were subjected to the synthesis process, using the tabular method. In Agenda 2030, when diagnosing the importance of this issue, one of 17 goals, i.e., goal 11, and 10 tasks within it, were devoted to the sustainable development of cities. The results of this study showed that sharing economy in tourism has an impact on the implementation of seven of them, but the direction of the impact is diversified. The domination of positive sharing economy (SE) effects was observed in the following areas: providing access to safe, affordable, accessible and sustainable transport systems for all (Target 11.2) and upgrading slums (Target 11.1), while the negative effects were noticed particularly clearly in implementing Targets 11.6 (reducing the adverse per capita environmental impact of cities) and 11.7 (providing universal access to safe, inclusive and accessible, green and public spaces).
Keywords: D12; D22; E21; L83; 330; Agenda 2030; sharing economy; sustainable city; sustainable development; tourism